Formulation and Evaluation of Lornoxicam Nanocrystals with Different Stabilizers at Different Concentrations (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To develop and evaluate nanocrystals of lornoxicam to improve solubility by converting pure drug of lornoxicam which is in micronized form to nanosized form. Materials and Methods: Saturation solubility of lornoxicam was evaluated by adding excess of the drug in 5 mL of different media (0.1 N HCl, phosphate buffer pH 6.8 and pH 7.4). Nanocrystals of lornoxicam were prepared successfully using polyvinylpyrrolidone (PVP) and Î²-cyclodextrin (BCD) as stabilizers by antisolvent precipitation method. The prepared nanocrystals were evaluated for their physicochemical characteristics such as physical appearance, Fourier transform infrared (FTIR), differential scanning calorimetry, scanning electron microscopy, X-ray powder diffractometry, solubility studies, particle size distribution, zeta potential, and in vitro drug release studies. Results and Discussion: This research work has been made to improve solubility by converting pure drug of lornoxicam which is in micronized form to nanosized form. The FTIR spectroscopy was used to confirm compatibility and to rule out any possible interactions between drug and polymers. Six nanocrystal formulations (PF1, PF2, PF3, BF1, BF2, and BF3) consisting pure drug of lornoxicam (micronized form) with PVP and BCD used as stabilizers in the ratios of 1:1, 1:2, and 1:3, respectively, were prepared. In vitro drug release from nanocrystals was carried out in different buffers, and the data obtained were fit into different equations and kinetic models to explain release kinetics. Lornoxicam with PVP and BCD in 1:3 ratio formulations in 7.4 pH phosphate buffer showed better solubility and emerged to be an ideal formulation for lornoxicam nanocrystals. Conclusion: From the study results, it can be concluded that optimized nanocrystals formulation of has improved solubility as compared to pure drug. The developed nanocrystals of lornoxicam found useful to improve solubility of lornoxicam.